How media coverage affects cross-sectional stock returns and momentum profits? - Sogalho, Inês Guedes de Pinho (2016)
This dissertation investigates the influence of the mass media coverage among NASDAQ common stocks on both cross-sectional of stock returns and momentum profits from January 2005 through December 2014. First, we relate the monthly stock return of each stock with the number of articles published about the firm during a given month. The findings suggest no clear relation between the amount of firm-specific news and its expected stock returns. A portfolio of stocks not covered in the media has on average a similar performance as a portfolio of stocks highly covered in the media. Additionally, we study the impact of media coverage on the momentum profits. We find that the momentum effect is stronger among firms highly covered by media. These results are both economically and statistically strong. Our results offer support to an overreaction-based explanation for the momentum effect